PENGARUH MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING TERHADAP KEMAMPUAN MENULIS TEKS EKSPLANASI SISWA KELAS VIII SMP SWASTA SANTA LUSIA SEI ROTAN - Fanny Naibaho; Rosmaini (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study aims to, (1) analyze the abilityl to write explanatoryl textsi for class VIII students of Santa Lucia Sei Rotan Privatel Middlel Schooll in the 2022/2023 academico yearl before usingi the Student Facilitator and Explaining model; (2) Analyzing the ability to write explanatory texts for class VIII students of Santa Lucia Sei Rotan Privatei Middle Schooll in the 2022/2023 academic year after using the Student Facilitator and Explaining modell; (3) Analyzingi the effect of the Student Facilitator and Explaining model on the ability to write explanatoryl texts for class VIII studentsl of Santa Lucia Sei Rotan Private Middle School in the 2022/2023 academici year. The research design used was a pre-experimentall designi with one group pretest-posttest. The population of this study were all students of class VIII SMP Santa Lucia Sei Rotan Private Middle Schooll. The sample of this research was 31 students of class VIII-2 by purposivei sampling. The resultsi of this study were analyzed usingi descriptive and inferential statistical analysis.